Improved Dominant Brightness Level Based Color Image Enhancemrnt Using Bilateral Filter (International Journal of Engineering and Computer Science, 2015)
Image enhancement plays a significant role in vision applications. It is used to improve the overall quality of the degraded images. Recently much work has been done in the field of remote sensing images enhancement. Many techniques were proposed so far for enhancing the remote sensing images. It has been found that the most of the existing techniques were based upon the transform domain methods; which may introduce the color artifacts and also may reduce the intensity of the input remote sensing image. To overcome this problem, a new integrated approach has been proposed which have the capability to enhance the contrast in remote sensing images in efficient manner by using the dominant brightness level analysis and gamma correction. The selection of the gamma correction seems to be justifiable as it has the ability to overcome the problem of reduction in illuminate of the existing methods. However to handle the short coming of transform domain method, bilateral filter has also been used to reduce the color artifacts. The algorithm has been designed and implanted in MATLAB using image processing toolbox. Comparative analysis has shown that proposed algorithm performs better as compared to existing techniques.